Anion Recognition and Induced Self‐Assembly of an α, γ‐Cyclic Peptide To Form Spherical Clusters. Issue 14 (4th March 2016) - Rodríguez‐Vázquez, Nuria; Amorín, Manuel; Alfonso, Ignacio; Granja, Juan R.
Abstract: A cyclic octapeptide composed of hydroxy‐functionalized γ‐amino acids folds in a "V‐shaped" conformation that allows the selective recognition of anions such as chloride, nitrate, and carbonate. The process involves the simultaneous self‐assembly of six peptide subunits and the recognition of four anions to form a tetrahedral structure, in which the anions are located at the corners of the resulting structure. Each anion is coordinated to three different peptides. The structure was fully characterized by several techniques, including NMR spectroscopy and X‐ray diffraction, and the material was able to facilitate the transmembrane transport of chloride ions. Abstract : A cyclic octapeptide has been shown to fold into a "V‐shaped" conformation that allows the selective recognition of anions such as chloride, nitrate, and carbonate. The selective anion recognition process involves the simultaneous assembly of six cyclic peptide subunits and four anions to give a supramolecular cluster that efficiently facilitates transmembrane transport of the anions.